Efectos y riesgo de desnutrición en el funcionamiento ejecutivo de niños entre 3 y 6 Años - Benavides Medina, Berenice (Universidad Antonio Nariño, 2023)
Several authors, both theoretical and empirical, demonstrate the importance of ensuring quality nutrition to children during their first years of life, especially because their optimal cognitive development will depend on it.